THE EFFECTIVENESS OF VOICE OF AMERICA NEWS VIDEO AS THE TEACHING MEDIA OF LISTENING ABILITY AT FIRST GRADE OF SMAN 1 BABAKAN - Misyfa bayani; Tohidin Masnun; Nana Priajana (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2018)
Abstract: Listening is considered as the most important skill and it is role as the beginning of the other skills. However, many students faced difficulties to master listening because they lack of vocabulary and students less pay attention. In this research was used VOA news video. Therefore, the objective of this research including 1) How is the effectiveness of using VOA news video on students listening ability? and 2) How is the studentâ€™s perception on the use of VOA news video on students listening ability?. This research is quasi experimental, The population of the research is all students of SMAN 1 Babakan 2017/2018, the sample are students of X IPA 1 consists of 36 students and X IPA 2 consists of 35 students. The instrument of this research is test; pre-test and post-test and questionnaire. The research findings showed that there is an effect from pre-test and post-test score in experimental class after being taught through VOA news video. The mean score of pre-test is 60,42 and the post-test is 87,14. The hypothesis test showed the significant score of regression was 0,000 because of significant score < 0,05 and t count (4,168) > t table (2,03452) thus, H0 rejected means that there is effect using VOA news video in students listening ability. In addition, the perception of the students, most of students responded agree of VOA news video as media teaching listening. Therefore, VOA news video is recommended as a media to be used by English teachers to teaching listening ability.Â Keywords: VOA News Video, Media, Teaching Listening Ability.